Variation in RNA polymerase sigma subunit composition within different stocks of Escherichia coli W3110. - Jishage, M (1997)
The composition of RNA polymerase sigma subunits was analyzed for stock strains of Escherichia coli K-12 W3110 in Japan. Heterogeneity was discovered with respect to two sigma subunits, sigma28 (sigmaF, the rpoF gene product) and sigma38 (sigmaS, the rpoS gene product). Five different types of W3110 were identified: A-type lineages have both sigma subunits in intact forms; B-type lineages carry a truncated sigma38 subunit and an intact sigma28 subunit; C-type lineages carry an intact sigma28 subunit but lack a sigma38 subunit; D-type lineages have only a sigma38 subunit without a sigma28 subunit; and E-type stocks lack both sigma subunits. All the lineages examined, however, contain the intact forms of sigma70 (sigmaD, the rpoD gene product) and sigma54 (sigmaN, the rpoN gene product). As expected from the lack of a sigma28 subunit, cells of D- and E-type lineages are nonmotile. The truncated form of the sigma38 subunit in B-type stocks carries two mutations near its N terminus and lacks C-terminal proximal region 4 due to an amber mutation. The failure of C- and E-type W3110 cells to express sigma38 and that of D- and E-type cells to express sigma28 were found to be due to defects in transcription even though the respective sigma subunit genes remain intact. These findings emphasize the importance of paying attention to possible variations in the genetic background between laboratory stocks originating from the same strain.